Bilateral olfaction: two is better than one for navigation - Raman, Baranidharan (BioMed Central, 2008)
Do animals require bilateral input to track odors? A recent study reveals that fruit fly larvae can localize odor sources using unilateral inputs from a single functional sensory neuron, but that an enhanced signal-to-noise ratio provided by dual inputs is helpful in more challenging environments.